Generation of Thermogravitational Convection and Convective Diffusion in a Radiation-Heated Region; Fluid Dynamics; Vol. 60, iss. 1 - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Salikhov F. Yu. Feliks Yurjevich (2025, 2025)
Title screen